Does Loneliness Lurk in Temp Work? Exploring the Associations between Temporary Employment, Loneliness at Work and Job Satisfaction - Eline Moens; Stijn Baert; Elsy Verhofstadt; Luc Van Ootegem (Institute of Labor Economics (IZA), 2019)
This research contributes to the limited literature concerning the determinants of loneliness at work, as well as to the literature on psychological outcomes associated with temporary work. More specifically, we are adding to the literature by exploring whether there is an association between working temporarily and loneliness at work and whether loneliness at work partly explains the association between working temporarily and job satisfaction. To this end, we analyse – by means of a mediation model – a unique sample of Flemish employees in the private sector. We find that employees with a temporary contract experience more loneliness at work as opposed to employees with a permanent contract. In addition, we discover that loneliness at work mediates the association between working temporarily and job satisfaction.
Keywords: J28; J41; I31; 330; loneliness at work; temporary work; job satisfaction